Opioid substitution treatment programs in Slovenia - Andrej Kastelic; Tatja Kostnapfel (Zdravniški Vestnik, 2010)
Background: Substitution maintenance treatment is considered to be one of the most effective options for the management of heroin or other opioid drug addiction. It has expanded substantially in the European Union in the last decade. It is part of recognised medical practice approved by competent authorities. Research has shown that methadone maintenance treatment is more effective than detoxification programmes in promoting retention in drug treatment and abstinence from illicit drug use. The death rate of people with opioid dependence under methadone maintenance treatment is one third to one fourth the rate of those not under treatment. IDUs who do not enter treatment are up to six times more likely to become infected with HIV and fifteen times more with hepatitis C than injectors who enter and remain under treatment. Criminal behaviour is strongly reduced. Every Euro invested in the programmes may yield a return of between four and seven Euros in reduced drug-related crime, criminal justice costs and theft alone, and when including savings related to health care, total savings can exceed costs by a ratio of 1:12. Conclusions: Since 1995 eighteen Centres for the Prevention and Treatment of Drug Addiction have been established in the Republic of Slovenia. Centre for Treatment of Drug Addicts at the University Hospital of Psychiatry in Ljubljana was established in 2003. Substitution treatment with methadone was introduced in Slovenia in 1990, buprenorphine was registered in 2004 and SR morphine in 2005. Since 2007 buprenorphine-naloxone combination has been used as well. In 2008 there were 4429 patients treated in these outpatient centres, 3332 of them with substitution medications and additionally 542 in prisons. At the Centre for treatment of drug addiction 790 patients were treated in the outpatient clinic, 174 as inpatients and 70 in the day hospital.